Participation of Women From Indigenous Peoples in the Formation of National Law - Tridewiyanti, Kunthi; Anggraeni, Ricca; Siyo, Suryanto; Pattinaja, Henri Christian (SASI, 2023)
Introduction: Discrimination against women from Indigenous Peoples in various ways of life including in the formation of national laws. This is due to the presence of a patriarchal culture which is reflected in laws and regulations both at the national and regional levels, thus showing injustice and inequality between men and women.Purposes of the Research:  The purpose of this writing is to explain the importance of the participation of indigenous and tribal women in the formation of national law. The importance of this participation will contribute to the thought of a legal substance that provides equality and justiceMethods of the Research: This paper uses doctrinal research methods using a feminist legal theory approach.Results of the Research: The results and findings in this paper include, First, the voices and experiences of indigenous and tribal women are required in feminist legal theory to influence non-discriminatory legal norms in the formation of national law. Second, the participation of indigenous and tribal women as part of the Indonesian nation has a strategic position guaranteed by the constitution to carry out their role in forming national law. This is a prerequisite and a representation of the realization of democratic government and one of the other principles of good governance that is consistent and committed to prioritizing the interests of the nation and the State.